Peran Alumni dalam Mengembangkan dan Meningkatkan Sumber Daya Manusia (SDM) Santri di Pondok Pesantren Anwarul Huda Malang - Wahyudi Widodo (Lembaga Yasin AlSys, 2026)
Although alumni hold a strategic position as partners of Islamic boarding schools in developing students’ human resources (HR), scholarly studies on the forms of their contributions and the impacts of their involvement remain limited. This study aimed to analyze the role of alumni in developing and improving the quality of students’ human resources at Pondok Pesantren Anwarul Huda Malang. The study employed a qualitative approach with a descriptive design. Informants were selected through purposive sampling and included the pesantren leader and administrators, alumni association administrators, alumni who actively contributed, and students. Data were collected through observation, in-depth interviews, and documentation and were subsequently analyzed using the interactive model of Miles, Huberman, and Saldaña, which comprises data collection, data condensation, data display, and conclusion drawing and verification. The findings indicate that alumni play a significant role in improving the quality of students’ human resources through five main forms of contribution: organizing guidance and skills-training activities, serving as mentors and resource persons based on their professional experience, participating as teachers at Madrasah Diniyah, providing financial support and facilities for pesantren development, and enhancing students’ motivation, insights, and career networks. These contributions positively affect students’ knowledge, skills, self-confidence, and readiness to engage in community life and the world of work. This study affirms that alumni involvement and the presence of an active alumni organization are important elements in sustaining synergy between alumni and the pesantren and supporting the continuous development of students’ human resources.